Sickness Absence and Search Unemployment - Bertil Holmlund (Uppsala University, Department of Economics, 2004)
The paper presents a model that allows a unified analysis of sickness absence and search unemployment. Sickness appears as random shocks to individual utility functions, interacts with individual search and labor supply decisions and triggers movements across labor force states. The employed worker prefers absence for sufficiently severe sickness and the unemployed worker may prefer nonparticipation if the disutility of search is amplified by sickness. The decisions governing labor force transitions are influenced by social insurance benefits available for sick or unemployed workers. We examine how these benefits affect individual decisions on absence and search and the implications for employment, unemployment and nonparticipation. The normative analysis of the socially optimal benefit structure suggests that there is, in general, a case for benefit differentiation across states of non-work. In particular, there is a case for a benefit structure that rewards active job search.
urn:nbn:se:uu:diva-4513
Keywords: J21; J64; J65; 330; Sickness absence; search; unemployment; sickness benefits; unemployment benefits; Fehlzeit; Krankheit; Arbeitsuche; Arbeitslosenversicherung; Theorie